Analysis of different infiltration effect for selective laser sintering process through Taguchi method. Issue 3 (1st September 2016) - Vennilaa, D. B.; Karuppusami, G.; Senthil, P.
Abstract: In this work, an attempt is made to improve the performance of the selective laser sintering process for the production of stainless steel part infiltrated with copper and its alloys. The main aim was to experimentally investigate the influence of selective laser sintering process parameters on hardness. Samples are produced for each experimental condition based on Taguchi's orthogonal array. It is noted that the infiltration material, laser scan distance, laser power and orientation angle are the process parameters that make considerable enhancement in hardness. The optimum selective laser sintering condition is found through the Taguchi method and mathematical model is also developed for the process. It is noted that the components produced for the optimum condition reveal considerable enhancement in hardness.